The media and the war on terrorism - Hess, Stephen; Kalb, Marvin L.; Brookings Institution; Joan Shorenstein Center on the Press, Politics, and Public Policy (Washington, D.C. : Brookings Institution Press, 2003)
"These candid conversations capture the difficulties of reporting during crisis and war, particularly the tension between government and the press. The participants include distinguished journalists - American and foreign, print and broadcast - and prominent public officials, past and present. They illuminate the struggle to balance freedom of the press and the right to know with the need to protect sensitive information in the national interest. As the Information Age collides with the War on Terrorism, that challenge becomes even more critical and daunting."--BOOK JACKET.
1. Introduction -- Pt. 1. The Media and the Government: World War II to the End of the Twentieth Century -- 2. Lessons of Wars Past / Peter Arnett, Stanley Karnow, Ted Koppel, Daniel Schorr and Barry Zorthian -- 3. Presidential Press Secretaries / Joe Lockhart, Michael McCurry, Dee Dee Myers and Ron Nessen -- 4. National Security Decisionmakers / Jeanne J. Kirkpatrick, James R. Schlesinger and R. James Woolsey -- 5. The CNN Effect / Lawrence S. Eagleburger, Claus Kleber, Steven Livingston and Judy Woodruff -- Pt. 2. War in Afghanistan: The Early Stages -- 6. The Pentagon and the Press / Victoria Clarke / Pentagon Military Officials and Washington News Bureau Chiefs -- 7. Three Months Later / Victoria Clarke, Michael Getler, Bernard Kalb and Sanford J. Ungar -- Pt. 3. The Journalist's Dilemma: Three Stories -- 8. The Hart-Rudman Commission Report / Thomas Kunkel, Susan Page, Warren B. Rudman and Bob Schieffer -- 9. The Anthrax Attacks and Bioterrorism / Ceci Connolly, Susan Dentzer, Kevin Keane and Jonathan B. Tucker -- 10. Dissent / Alex Arriaga, Peter D. Hart, Mark Jurkowitz, Geneva Overholser and Robert Siegel -- Pt. 4. Reporting from the Field: Three Sites -- 11. Afghanistan / Michael Gordon, Carol Morello, Lois Raimondo, Tom Squitieri and Kevin Whitelaw -- 12. The Middle East / Glenn Frankel, Todd Purdum, David Shipler and Robin Wright -- 13. Foreign Correspondents in Washington / Hafez Al-Mirazi, Jose Carreno, Yasemin Congar, Toby Harnden, Rudiger Lentz, Jean-Jacques Mevel and Andrei K. Sitov -- Pt. 5. From Different Perspectives -- 14. Public Diplomacy or Propaganda? / Karen DeYoung, Thomas A. Dine, Joseph Duffey and Christopher Ross -- 15. Congress / Candy Crowley, Thomas Donilon, Mort Kondracke and James Lindsay -- 16. Public Opinion / Jill Abramson, David S. Broder, Margaret Carlson, Andrew Kohut, William Kristol and Tom Rosenstiel -- 17. Overview / Lloyd N. Cutler, Lee H. Hamilton, Harry C. McPherson and James Sasser -- Pt. 6. 9/11 and Beyond -- 18. Running toward Danger / E. J. Dionne Jr., John McWethy, Alan Murray and Alicia C. Shepard.
"Cosponsored by the Shorenstein Center on the Press, Politics, and Public Policy at Harvard University."
Includes bibliographical references and index.
Keywords: Terrorism -- Press coverage; War -- Press coverage; Terrorism and mass media